Efficacy of Intra-cameral Mydriatic and Anesthetics- in Small Incision Cataract Surgery (SICS) - Mahmud ul Huda, Md; Abdul Khaleque, Sajed; Zinnurain, Md; Hossain, Md Musharraf; Jannat Munjifa, Rowjatul (Medicine Today, 2025)
Introduction: Aim: To observe the per operative efficacy (in term of time of papillary dilatation and its maintenance till end of the surgery) of intra-cameral mydriatic and anesthetics(tropicamide 0.02%, phenylephrine 0.31% and lidocaine 1%) (ICM) in small incision cataract surgery (SICS). Materials and Methods: This is a cross sectional analytical study done in the department of ophthalmology Sheikh Hasina Medical College Jamalpur, from 27 April 2022 to 24 May 2022. This study includes 52 eyes of 52 patients. All patients received 0.2 ml intra cameral injection of mydriatic and anesthetic after opening anterior chamber. The pupillary size was measured periodically upto the end of the surgery with caliper. Result : The mean pupil diameter was 7.6 mm±0.72 before capsulorhexis, 7.3mm± 0.78 before lens implantation and 7mm± 0.83 before sub-conjunctival injection(at the end of the surgery). In 94.2 % of the cases papillary diameter was achieved and maintained ≥6mm till the end of the surgery. Conclusion: Intra-cameral combination of tropicamide0.02%, phenylephrine 0.31% and lidocaine 1% could be a good alternative of standard regimen in SICS. Medicine Today 2025, Vol.37 (1): 23-26